PENGARUH METODE QIRA’AH TERHADAP PEMAHAMAN PESERTA DIDIK TENTANG ISM NAKIRAH DAN MA’RIFAH - Marni, Marni (IAIN Bone, 2020)
This article examines the effect of the qira'ah learning method on students' understanding of ism nakirah and ma'rifah. This study aims to determine the effect of the qira'ah learning method on students' understanding of ism nakirah and ma'rifah. This research is experimental with a quasi experimental design model. The population of this study were students, consisting of the control class and the experimental class, the control class did not use the qira'ah method, while the experimental class used learning using the qira'ah method. The purpose of this study was to identify in general the differences in the understanding of students about ism nakirah and ma'rifah who use conventional learning with the tarjamah method with learning through the qira'ah method. It is proven by the existence of significant data, namely the conventional learning of the tarjamah method for class Xb or control class with an average of 4,844, and for the experimental class Xa using the qira'ah method an average of 6,677. Thus, it is concluded that the use of the qira'ah method has a significant effect on the understanding of ism nakirah and ma'rifah.